A Novel Compound, Tanshinol Borneol Ester, Ameliorates Pressure Overload-Induced Cardiac Hypertrophy by Inhibiting Oxidative Stress via the mTOR/β-TrCP/NRF2 Pathway - Han, Dongjian; Wang, Fuhang; Wang, Bo; Qiao, Zhentao; Cui, Xinyue; Zhang, Yi; Jiang, Qingjiao; Liu, Miaomiao; Shangguan, Jiahong; Zheng, Xiaohui; Bai, Yajun; Du, Chunyan; et al. (Frontiers in Pharmacology, 2022)
Tanshinol borneol ester (DBZ) exerts anti-atherosclerotic and anti-inflammatory effects. However, its effects on cardiac hypertrophy are not well understood. In this work, we investigated the treatment effects and potential mechanisms of DBZ on the hypertrophic heart under oxidative stress and endoplasmic reticulum (ER) stress. A hypertrophic model was established in rats using transverse-aortic constriction (TAC) surgery and in neonatal rat cardiomyocytes (NRCMs) using angiotensin II (Ang II). Our results revealed that DBZ remarkably inhibited oxidative stress and ER stress, blocked autophagy flow, and decreased apoptosis in vivo and in vitro through nuclear NRF2 accumulation, and enhanced NRF2 stability via regulating the mTOR/β-TrcP/NRF2 signal pathway. Thus, DBZ may serve as a promising therapeutic for stress-induced cardiac hypertrophy.